Wear and reliability of cylindrical vehicle joints - Dykha, A.; Padgurskas, J.; Kukurudzyak, Yu.; Babak, O. (Problems of Tribology, 2020)
A method for calculating the wear of car suspension liners is presented. To determine the wear by a computational method, a system of equations for the spherical contact of mates of the friction unit of a car was obtained. An example of calculating wear for a given service life of a ball joint is given. The issue of determining the reliability indicators of a cylindrical hinge by the wear criterion is considered. An experimental study of the effectiveness of various greases for car hinge joints has been carried out